Global criminal and sovereign free economies and the demise of the Western democracies: dark Renaissance - Bunker, Robert J. (Routledge advances in international political economy, 2015)
"Drawing together experts from a variety of backgrounds, this work explores the increasing shift away from formal based capitalism and evaluates through case studies how different states are responding to the challenges they face"--